2008
DOI: 10.1111/j.1460-2695.2007.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Cruciform fillet welded joint fatigue strength improvements by weld metal phase transformations

Abstract: A B S T R A C T Arc welding typically generates residual tensile stresses in welded joints, leading to deteriorated fatigue performance of these joints. Volume expansion of the weld metal at high temperatures followed by contraction during cooling induces a local tensile residual stress state. A new type of welding wire capable of inducing a local compressive residual stress state by means of controlled martensitic transformation at relatively low temperatures has been studied, and the effects of the transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Ohta et al [8] adopted 10Cr10Ni LTT welding wire and doubled the fatigue strength of corner boxing fillet joint of high-strength steel HT780. Darcis et al [12] reported their results on the fatigue strength of cruciform fillet welded joints using three types of LTT welding wires with Ms temperature in the range 270–360°C. It was found that the fatigue life of LTT welded joints was at least three times longer than that of specimens using conventional welding wire.…”
Section: Introductionmentioning
confidence: 99%
“…Ohta et al [8] adopted 10Cr10Ni LTT welding wire and doubled the fatigue strength of corner boxing fillet joint of high-strength steel HT780. Darcis et al [12] reported their results on the fatigue strength of cruciform fillet welded joints using three types of LTT welding wires with Ms temperature in the range 270–360°C. It was found that the fatigue life of LTT welded joints was at least three times longer than that of specimens using conventional welding wire.…”
Section: Introductionmentioning
confidence: 99%
“…Alberry and Jones reported that a reduction in processing temperature can drive the suppression of residual stresses [12]. Low-transformation-temperature (hereinafter LTT) welding consumables that exploit this phenomenon have been developed in recent years [13][14][15][16][17]. Conventional consumables have a transformation temperature of about 500 o C, but in an LTT welding material with Fe-10Ni-10Cr (wt.%) developed by Ohta et al, phase transformation occurred at 180 o C [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to prevent unstable fractures, welding residual stress distribution needs to be controlled. To date, some studies have investigated the possibility of using low transformation temperature (LTT) welding to decrease the tensile stress in weld joints, strengthening their mechanical properties and reducing their stress regarding distortion, cracking, and fatigue to improve relevant performance [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%